PENGARUH CAPITAL ADEQUACY RATIO (CAR), FINANCING TO DEPOSIT RATIO (FDR), NON PERFOMING FINANCING (NPF), BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSET (ROA) PADA BANK UMUM SYARIAH TAHUN 2015-2018 - Rudi Ramadhani; Amelia Anwar; Eka Travilta Oktaria (Universitas Mitra Indonesia, 2021)
This study aims to determine the effect of knowing the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Operational Expenditures on Operating Income (BOPO) on Return on Assets (ROA) at Banks Sharia General in 2015-2018. This study uses quantitative data with secondary data sources in the form of financial statements. The sampling technique used was purposive sampling and obtained a sample of 4 Islamic banks. Data taken from quarterly financial reports obtained from the official website of each bank is a research sample. The results of this study show that the results of the test simultaneously (Test F) obtained F count 73,367 f table 2,53 with a significant result of 0,000 0,05, which means that CAR, FDR, NPF and BOPO jointly influence and significant to ROA. While the test results t (1) CAR has a value of t count 2.195 t table 2.00172 with a significant level of 0.032 0.05, which means that CAR has a positive and significant effect on ROA. (2) FDR has a value of t count 2.333 t table 2.00172 with a significant level of 0.023 0.05, which means that FDR has a positive and significant effect on ROA. (3) NPF has a value of t count 1.437 t table 2.00172 with a significant level of 0.156 0.05, which means that NPF has no effect and is not significant towards ROA. (1) BOPO has a value of t count -14.915 t table 2.00172 with a significant level of 0,000 0.05 which means that BOPO has a negative effect and is significant for ROA.Keywords: CAR, FDR, NPF, BOPO and ROA